2D mapping of radiation dose and clonogenic survival for accurate assessment of in vitro X-ray GRID irradiation effects. (21st January 2023) - Arous, Delmon; Lie, Jacob Larsen; Håland, Bjørg Vårli; Børsting, Magnus; Edin, Nina Frederike Jeppesen; Malinen, Eirik
Abstract: Spatially fractionated radiation therapy (SFRT or GRID) is an approach to deliver high local radiation doses in an 'on-off' pattern. To better appraise the radiobiological effects from GRID, a framework to link local radiation dose to clonogenic survival needs to be developed. A549 lung cancer cells were irradiated in T25 cm 2 flasks using 220 kV x-rays with an open field or through a tungsten GRID collimator with periodical 5 mm openings and 10 mm blockings. Delivered nominal doses were 2, 5, and 10 Gy. A novel approach for image segmentation was used to locate the centroid of surviving colonies in scanned images of the cell flasks. Gafchromic TM film dosimetry (GFD) and FLUKA Monte Carlo (MC) simulations were employed to map the dose at each surviving colony centroid. Fitting the linear-quadratic (LQ) function to clonogenic survival data for open field irradiation, the expected survival level at a given dose level was calculated. The expected survival levels were then mapped together with the observed levels in the GRID-irradiated flasks. GFD and FLUKA MC gave similar dose distributions, with a mean peak-to-valley dose ratio of about 5. LQ-parameters for open field irradiation gave α = 0.24 ± 0.02 Gy −1 and β = 0.019 ± 0.002 Gy −2 . The mean relative percentage deviation between observed and predicted survival in the (peak; valley) dose regions was (4.6; 3.1) %, (26.6; −1.0) %, and (129.8; −2.3) % for 2, 5 and 10 Gy, respectively. In conclusion, a framework for mapping of surviving colonies following GRID irradiation together with predicted survival levels from homogeneous irradiation was presented. For the given cell line, our findings indicate that GRID irradiation causes reduced survival in the peak regions compared to an open field configuration.